Thermal limits to stoloniferous leaves and root growth in Paspalum notatum, a south American native grass - Áurea Rodrigues Cordeiro; Alexandre Aparecido Duarte; Ana Paula de Faria; José Pires de Lemos Filho; Marcel Giovanni Costa França (Tropical Grasslands-Forrajes Tropicales)
In tropical regions the cultivation of African grasses for animal forage is extensive and an ecophysiological alternative is to stimulate the use of native species especially in a scenario of global temperature change. The thermal limits to leaf and root growth in Paspalum notatum a South American native grass were evaluated. Stolon fragments with roots and dry parts removed and the same number of nodes were placed in transparent plastic boxes on moistened filter papers and transferred to chambers at constant temperatures of 15, 20, 25, 30, 35 °C and alternating temperatures of 25/15 °C and 30/20 °C, all in a 12 h photoperiod. Leaf production was evaluated daily for 30 days. Stolon fragments showed leaf growth in all temperatures, except at 15 °C. The thermal range limits were 14.3 °C as base temperature and 39.2°C as ceiling temperature. Results showed that 50 degree days were necessary for 50% of leaf growth by the stolons. The largest leaf area occurred at 25 to 30 °C and the largest specific leaf area was at 25 °C. The optimal temperature for growth was 30 °C with higher root growth at 20 °C and in alternating temperatures. Results indicate that P. notatum has potential to grow in a wide range of temperatures and that the increase of global average temperature should not affect its distribution in its current habitat, presenting promising traits as an option for pastures in all tropical regions.